Speech at the Session on China’s Economy, Promoting Reforms in Major Areas, and Accelerating the Shift in Driving Forces for Development - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group (WBG), offered several strategic considerations for China. First, for the foreseeable future, removing distortions and accelerating diffusion will remain major sources of growth. Getting the basics right – structural reforms in key markets, further improving the broader business environment, ensuring fair competition, and investing in broad-based skills of the labor force – should help drive growth. Second, China should consider how to balance industrial policies with the notion of the third plenum, that the market should play a decisive role in resource allocation. Third, like other countries, China needs to prepare for how technological change will impact the labor force. He concluded by saying that China’s leadership has been critical to promoting an open, competitive global economy.